2015
DOI: 10.1007/s40090-015-0052-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics and density functional theory study on the corrosion inhibition of austenitic stainless steel in hydrochloric acid by two pyrimidine compounds

Abstract: Quantum chemical calculations based on density functional theory method were performed on two pyrimidine derivatives which may be used as corrosion inhibitors for austenitic stainless steel. The quantum chemical properties of the two pyrimidine derivatives that are most relevant to their potential action as corrosion inhibitors have been calculated. To explain the inhibition performance of the pyrimidine derivatives, their local reactivities were analyzed through Fukui functions. The binding energies of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…The theoretical report of Shojaie et al [ 50 ] indicated that the molecules with N atoms are preferentially protonated in acidic medium, contrary to the behaviour of compounds with S and O atoms. The researchers conducted the analysis of two pyrimidine derivatives (S and N compounds) and observed that there was a correlation between the molecular mass and the inhibition efficiency; the adsorption on the metal surface improved as the molecular mass increased.…”
Section: Multi-heteroatom-containing Corrosion Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The theoretical report of Shojaie et al [ 50 ] indicated that the molecules with N atoms are preferentially protonated in acidic medium, contrary to the behaviour of compounds with S and O atoms. The researchers conducted the analysis of two pyrimidine derivatives (S and N compounds) and observed that there was a correlation between the molecular mass and the inhibition efficiency; the adsorption on the metal surface improved as the molecular mass increased.…”
Section: Multi-heteroatom-containing Corrosion Inhibitorsmentioning
confidence: 99%
“…They associated a higher number of heteroatoms in a molecule with its superior interaction capacity with a metallic surface. Atoms with the highest negative partial atomic charge interact more strongly with a metallic surface through a donor–acceptor interaction [ 50 ]. Caliskan et al [ 14 ] noticed in their experimental study of pyrimidine derivatives that these compounds work as mixed-type inhibitors, both cathodic and anodic reactions were influenced by the presence of compounds in the corrosive medium, being the anodic effect the most significant behaviour.…”
Section: Multi-heteroatom-containing Corrosion Inhibitorsmentioning
confidence: 99%
“…A mixture of 5 11 (1 mmol), benzaldehyde (1 mmol) and anhydrous sodium acetate (1 mmol) in glacial acetic acid (10 ml) was heated under reflux for 4 h. The reaction mixture was kept overnight and the solid, thus separated, was filtered, washed with water and recrystallized from ethanol. (8). The 4-(6-benzoyl-3-oxo-7-phenyl-2,3-dihydro-5H-thiazolo-[3,2-a]pyrimidin-5-yl)benzoyl chloride (7) was obtained by the reaction of 5 with thionylchloride.…”
Section: -(6-benzoyl-2-benzylidene-3-oxo-7-phenyl-23-dihydro-5h-thimentioning
confidence: 99%
“…Very useful information can be obtained by the quantum chemical calculations to examine the corrosion inhibiting effects of organic compounds. The quantum chemical parameters all compounds such as μ, I, A, χ, η, w, S, ΔN and ΔE backdonation were calculated according to Shojaie et al 8 (Table I).…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation